FITNESS STATUS, LEVEL OF PHYSICAL ACTIVITY, AND ANTHROPOMETRICAL CHARACTERISTICS OF TPB ITB STUDENTS - PERMANA (NIM : 21714303), TAUFIK
Background: Physical activities are body movements that are created by skeletal muscles that require energy release. The lack of physical activities and low levels of fitness among high school students are considered as a trigger to low levels of fitness among TPB ITB students. This research aims to find out the average status of physical activities, anthropometry, fitness levels, and health status of TPB ITB students before and after MKOR. Method: 3447 TBP ITB students (male: 18,01 ± 0,69 years old; 169,27 ± 13,11 cm of height; 63,65 ± 14,27 kg of weight) and (female: 18,03 ± 0,65 years old; 159,38 ± 6,87cm of height; 52,99 ± 9,03 kg of weight) participated in the research. The data of physical activities are obtained from the International Physical Activity Questionnaire (IPAQ). This research used One Group Pretest-Posttest Design by performing the first and last test using Cooper Test 2400 meter to find the average value of the students’ fitness levels that is drawn by VO2Max. Result: The male students have an average BMI (Body Mass Index) of 21,80 ± 3,79 and the female students 20,74 ± 3,00. The average value of physical activities of these male students in high school was 1520,80 ± 1444,50 and in TPB ITB 2330,00 ±1800,77, whereas female students 1029,55 ± 1000,82 and 2020,46 ± 1895,68 respectively. The average fitness level of the male students during the first test is 35,34 ± 5,74 and the last test 38,27 ± 7,08, whereas the female students 28,60 ± 4,06 and 30,17 ± 5,17 respectively. 66,79% of TPB ITB students have a good health status, 22,88% have an ailment with a moderate-risk level, and 10,33% have an ailment with a high-risk level. Conclusion: TPB ITB students have a normal BMI and a good health status that can be seen through the significant increase of VO2Max.